1993
DOI: 10.1099/00221287-139-9-2055
|View full text |Cite
|
Sign up to set email alerts
|

The giant linear plasmid pHG207 from Rhodococcus sp. encoding hydrogen autotrophy: characterization of the plasmid and its termini

Abstract: As described previously, in Rhodococcus sp. (formerly Nocardia opaca) strains MRll and MR22, the ability to grow as an aerobic hydrogen bacterium (the Aut character) is located on giant conjugative linear plasmids -on pHG201 (270 kb) in strain MRll and on pHG205 (280 kb) in strain MR22. In an autotrophic transconjugant originating from MR22 a smaller plasmid, pHG207 (225 kb), was detected and shown to be a recombination product of the wild-type plasmids pHG204 and pHG205. A donor carrying pHG207 as the sole pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…Several diVerent Rhodococcus megaplasmids are known to be conjugative (Dabrock et al, 1994;Desomer et al, 1988;Kalkus et al, 1993;Priefert et al, 2004;Shimizu et al, 2001). The sequences and gene annotations of Wve rhodococcal megaplasmidsp33701 from Rhodococcus equi ATCC33701 (Takai et al, 2000), pBD2 from Rhodococcus erythropolis BD2 (Stecker et al, 2003), pRHL3 from Rhodococcus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Several diVerent Rhodococcus megaplasmids are known to be conjugative (Dabrock et al, 1994;Desomer et al, 1988;Kalkus et al, 1993;Priefert et al, 2004;Shimizu et al, 2001). The sequences and gene annotations of Wve rhodococcal megaplasmidsp33701 from Rhodococcus equi ATCC33701 (Takai et al, 2000), pBD2 from Rhodococcus erythropolis BD2 (Stecker et al, 2003), pRHL3 from Rhodococcus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Even plasmids with very similar ends may be the product of a recombination process, as was shown for pHG207. The two ends of pHG207 share 95 and 91 % identical base pairs over two regions of 237 and 329 positions, respectively; however, restriction analysis confirmed that the left and right end in fact originate from pHG204 and pHG205, respectively (Kalkus et al, 1993).…”
Section: +Sds +Sdsmentioning
confidence: 87%
“…The R. opacus wild-type strains MR11 and MR22 were each shown to contain three linear plasmids, pHG201 (270 kb), pHG202 (400 kb) and pHG203 (420 kb), as well as pHG204 (190 kb), pHG205 (280 kb) and pHG206 (500 kb), respectively (Kalkus et al, 1990). Two of these plasmids, pHG201 and pHG205, as well as pHG207, obtained from the transconjugant strain MR2253 (Kalkus et al, 1993), enable their hosts to grow chemolithoautotrophically on gaseous hydrogen and carbon dioxide. Furthermore, pHG204 correlates with thallium resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations